2006
DOI: 10.1074/jbc.m508571200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Expression of a Family of Nicotinic Acetylcholine Receptor Subunits in the Central Nervous System of the Mollusc Lymnaea stagnalis

Abstract: We described a family of nicotinic acetylcholine receptor (nAChR) subunits underlying cholinergic transmission in the central nervous system (CNS) of the mollusc Lymnaea stagnalis. By using degenerate PCR cloning, we identified 12 subunits that display a high sequence similarity to nAChR subunits, of which 10 are of the ␣-type, 1 is of the ␤-type, and 1 was not classified because of insufficient sequence information. Heterologous expression of identified subunits confirms their capacity to form functional rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 56 publications
3
47
0
Order By: Relevance
“…The acetylcholine receptors (AChRs) are particularly often involved in toxic effects of bioactive substances, like animal venoms, plant toxins, and also by neonicotinoid type insecticides (Daly 2005;Dutertre and Lewis 2006;Tomizawa and Casida 2003). The basic structural and pharmacological information on AChRs initially arose from vertebrates (Dani, 2001), but further studies suggest their much higher diversity in invertebrates (van Nierop et al, 2006;Wu and Lukas, 2011;Holden-Dye et al, 2013). In insects, moreover, molecular studies have also revealed taxonomical differences among the subclasses of nACh receptors (Dupuis et al, 2012;Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acetylcholine receptors (AChRs) are particularly often involved in toxic effects of bioactive substances, like animal venoms, plant toxins, and also by neonicotinoid type insecticides (Daly 2005;Dutertre and Lewis 2006;Tomizawa and Casida 2003). The basic structural and pharmacological information on AChRs initially arose from vertebrates (Dani, 2001), but further studies suggest their much higher diversity in invertebrates (van Nierop et al, 2006;Wu and Lukas, 2011;Holden-Dye et al, 2013). In insects, moreover, molecular studies have also revealed taxonomical differences among the subclasses of nACh receptors (Dupuis et al, 2012;Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…the pond snail, Lymnaea stagnalis or the edible snail, Helix pomatia) the identifiable giant neurons (with diameters up to 100 µm) allow potential toxic effects to be examined using intracellular electrophysiology techniques. Acetylcholine is a neurotransmitter and modulatory substance both in the CNS and the periphery of these organisms; moreover, cholinergic receptor subtypes including nAChRs have also been established (Walker et al, 1996;Vulfius et al, 2005;van Nierop et al, 2006;Krajcs et al, 2014). Therefore the identifiable snail neurons provide a suitable tool to characterize the interactions between the ACh receptors (AChRs) and potentially toxic substances including heavy metals, insecticides or mycotoxins (Arvanov et al, 1993;Gyori et al, 1994;Gyori et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Frustratingly, the heterologous expression of invertebrate nAChRs has proved to be extremely difficult [59,95] and, in several instances, this has often been achieved only by co-expression with vertebrate nAChR subunits [65,91,96,97]. More recently, expression studies in Xenopus oocytes have identified a family of anion-selective nAChRs, cloned from both the nematode Caenorhabditis elegans [98] and the mollusc Lymnaea stagnalis [99,100].…”
Section: Expression Of Recombinant Nachrs In Xenopus Oocytesmentioning
confidence: 99%
“…Pharmacological and immune data therefore were further supported by the presence of transcript in the FM coding for the LnAChR A subunit. The LnAChR A subunit is related to the homo-oligomeric human α7 nAChR and when expressed in oocytes it Acta Biologica Hungarica 67, 2016 is activated by cytosine and nicotine and blocked by αBgTX, αCTX-IMI [94]. However the nAChR in the snail FMs desensitizes slowly and also conducts Na + along with Ca 2+ , suggesting that the receptor is not a homopentamer [49].…”
Section: Nicotinic Acetylcholine Receptors Containing Functional α7-lmentioning
confidence: 99%